Perception of Students towards Entrepreneurship Courses: A Case Study of Pokhara University Business Students in Kathmandu - Upreti, Devendra (Nepalese Journal of Management, 2025)
This study examines the perceptions of business students at Pokhara University regarding entrepreneurship courses, focusing on the relationship between these perceptions and various influencing factors. Perception of entrepreneurship course is the dependent variable, while the independent variables are course content, teaching quality, learning environment, student characteristics, institutional support, and instructor experience. The study uses primary data from 146 respondents to assess their opinions on these variables in the context of Pokhara University in Kathmandu. A structured questionnaire was prepared for data collection. Descriptive statistics, Kendall’s Tau correlations, and regression models were used to test the significance and importance of students’ perceptions of entrepreneurship courses in Kathmandu. The findings indicate that course content is positively correlated with the perception of entrepreneurship courses, suggesting that enhanced course content leads to a more favourable perception of entrepreneurship course. Teaching quality also has a positive impact on perception of entrepreneurship course, implying that higher teaching quality results in a better perception of entrepreneurship courses. Similarly, the learning environment positively affects perception, indicating that a better learning environment leads to a more favourable view of these courses. Student characteristics is positively correlated with perception of entrepreneurship course. Additionally, institutional support positively influences perception, suggesting that increased support enhances students’ views of entrepreneurship courses. Lastly, instructor experience positively affects perception of entrepreneurship course, indicating that greater experience leads to a more favourable perception of these courses.